Design Proposal of a Prototype for Sawdust Pellet Manufacturing through Simulation - J. C. Paredes-Rojas; C. R. Torres San Miguel; A. I. Flores Vela; B. Bravo-Díaz; C. De la Cruz Alejo; D. Palma Ramírez (Advances in Materials Science and Engineering)
Mexican industry generates tons of organic wastes that are not used and cause social, environmental, and health problems. The main organic residue which is generated during wood production is the sawdust (biomass). In order to reduce the problems generated by its waste, a prototype to manufacture biofuel pellets was designed by considering a flat die pelletizing machine according to the standard EN 14961-2. The machine design consists of stainless steel 304 and carbon steel to produce pellets of 6 mm and 30 mm in diameter and length, respectively, at 50–100 rpm. The matrix types proposed were radial, spiral, and hexagonal. In order to be constructed quickly, the design is standardized. Results from finite-element analysis indicate that it is possible to manufacture pellets from 50 to 1000 PSI (344.7 kPa to 6894.7 kPa) with this design complying with the standard.